Medicamente și tratamente alternative pentru ulcerul peptic - Sergiu Aurel Orasan - Alic (Romanian National Association of the Veterinary Products Manufacturers, 2021)
Peptic ulcer is a chronic disease that affects up to 10% of the world's population. The appearance of peptic ulcer is dependent on the presence of gastric juice and its pH and the decrease of the mucosal defense. Two major factors recognized as disruptors of mucosal resistance are nonsteroidal antiinflammatory drugs (NSAIDs) and Helicobacter pylori (H. pylori) infection. The main conventional treatments for peptic ulcer, such as proton pump inhibitors (PPIs) and histamine-2 (H2) receptor antagonists, are associated with side effects, recurrences and various drug interactions. On the other hand, medicinal plants and their chemical compounds are useful in the prevention and treatment of many diseases. Therefore, this article presents some medicinal herbs that can be used for the treatment or prevention of peptic ulcers.